The Impact of Literature Circles Technique in Speaking Skills - Alpaslan Okur; Latif Yardım (Sakarya University Journal of Education)
This study aims to reveal the effects of literature circles in students’ speaking skills. The study was designed as a holistic single case study of qualitative data analysis method. Descriptive analysis was used in the analysis of the data. The group of the study consists of 29 secondary school students which are 16 female and 13 male students in 7th grade (Mostly 7th-grade students 12-13 years old) in a Turkish public school. Literature circles continued for 12 weeks. Data were collected by qualitative observation and used a semi-structured “speaking skills assessment form” Yıldız (2003, p. 404). Assessments and ratings of the speaking skills of the students made by the Turkish literacy teacher of the students at the beginning of literature circles and at the end of literature circles (pre-assessment and post-assestment). Data of 24 students who were in both the pre-assesment and the post-assessment were used. The results of the study show that literature circles contributed to the speaking skills of the class, have a dramatic contribution to developing students in their weak aspect of speaking skills. It is seen that as systematic practice literature circles develop students’ speaking skills in different aspects.